Pulmonary Complications of Systemic Lupus Erythematosus - Hannah, Jennifer R.; D'Cruz, David P. (Seminars in Respiratory and Critical Care Medicine, 2019)
Systemic lupus erythematosus (SLE) is an autoimmune rheumatic disease characterized by the production of pathogenic autoantibodies and immune complexes and is responsible for significant morbidity and mortality through a wide range of clinical manifestations which can affect almost any organ. Pulmonary involvement is prevalent and seen in 50 to 70% of SLE patients and may even be the presenting feature in 4 to 5% of patients. By 10 years postdiagnosis, 12% will have accumulated an element of permanent lung damage. Pulmonary complications are broad and include pleural disease, interstitial lung disease (ILD), vasculitis, pulmonary embolism, pulmonary hypertension, large airway disease, shrinking lung syndrome, and infection. Conditions can range mostly from asymptomatic, for example, in mild cases of pleural effusion or obstructive airway disease, to life-threatening disease, for example, in acute lupus pneumonitis or diffuse alveolar hemorrhage. ILD and pulmonary hypertension are both frequently seen in other autoimmune rheumatic diseases such as systemic sclerosis; however, in SLE, they tend to be milder and have a comparatively favorable prognosis. Although collectively pulmonary involvement in SLE is common, the heterogeneity of SLE and rareness of individual complications make clinical trials difficult and treatment is usually based on case series reports and anecdotal experience with various immunosuppressive agents. Some of these immunosuppressive agents such as azathioprine, methotrexate, and cyclophosphamide have also been linked with drug-induced lung injury.
Keywords: systemic lupus erythematosus; pulmonary disease; complications; interstitial lung disease; pleural disease